Wear properties of Boron added high strength low alloy (HSLA) SAE 8620 steel - Musa, Munzali; Mohammed, Abubakar Gambo; Muhammad, Auwal (Journal of Metals, Materials and Minerals, 2018)
The High Strength Low Alloy (HSLA) SAE 8620 steel with different contents of boron in ppm rate used in bearings, automotive gearing and automotive body components applications were studied. We report the relationship between wear properties, microstructural characterization and hardness properties of the steel. The steel chemical composition is selected to obtain relatively high mechanical properties with different boron contents. Increasing the normalization temperature and boron content, shows ferrite grain-size becomes larger when compared to lower normalization temperatures and boron content. With differences in boron content, only 2 HBN were measured from the average hardness of 3.3 ppm and 13.5 ppm, this clearly indicates normalization temperature has a great influence on the hardness. The boron inhibits the nucleation of ferrite at the boundary of austenite grain also increases the depth in which the steel hardened, the samples that are hardened have decrease in maximum frictional force and maximum coefficient of friction with increased boron content. The results from the high temperature studies indicate that the friction is dependent on temperature since a reduced friction level was observed with increasing temperature. Moreover, the sliding distance has no marginal effect on friction (differences for the max. coefficient of friction is small).